DIVERSITY MACROFAUNA AND CHEMICALS OF SOIL INFLUENCED BY TYPES OF SHADE PLANT IN ARABICA COFFEE PLANTATION - Halimatus Syahdia Hasibuan; Dewi Rezki; Nadiya Pirhat; Muhammad Parikesit Wisnubroto (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2026)
Soil macrofauna are an essential biotic component that plays a significant role in maintaining soil ecosystem balance. They are also among the most sensitive indicators of land-use change and can therefore be utilized as markers or predictors of soil quality. The diversity and abundance of soil macrofauna are generally influenced by environmental conditions, particularly vegetation covering or shading above the soil surface. Coffee cultivation in Solok Radjo, Kabupaten Solok, Sumatra Barat, is typically carried out under shade provided by various tree species. This study aimed to examine the diversity, abundance, and composition of soil macrofauna within coffee cultivation systems under different types of shade in Solok Radjo. The research was descriptive in nature and employed an exploratory method, with sampling conducted directly in the field using manual hand sorting. The shade conditions observed included unshaded, shade Paraserianthes falcataria, shade Eucalyptus sp., and shade Leucaena leucocephala. The findings revealed two phyla of soil macrofauna comprising 4 classes, 8 orders and 9 families. Soil macrofauna in coffee plantations with shades of Falcataria moluccana and Leucaena leucocephala trees had higher family counts, abundance, diversity index, and richness index compared to Eucalyptus sp. trees and unshaded. The evenness index was even across all shade types, with no dominant species. The organic carbon content was highest in the shaded areas of Falcataria moluccana trees. Agroforestry systems of coffee plants with shaded areas of Falcataria moluccana and Leucaena leucocephala trees can be implemented to stabilize microclimate conditions and increase litter volume, macrofauna biodiversity, and soil fertility.